The peregrinations of Guy Bernède, actor and witness of televisual cooperation in the post-independence period. From Ocora Television to FR3 Dom-Tom (1962-1975) - (:unkn) unknown (My University, 2021)
In the late 1950s, as France dismantled its empire and the African member states of the French Community were on the verge of gaining independence, the development of television accelerated. As a result of this historical contingency, the new national televisions in Francophone Africa and the French foreign broadcast sector were intertwined and impacted together in the aftermath of independence, in the context of the wider geopolitical Cold War order. This article seeks to follow Guy Bernède, actor and witness of the bilateral televisual cooperation in the post-independence period, from the creation of Ocora Television in 1962 to that of FR3 Dom-Tom in 1975. His itinerary shows the reconfigurations of televisual cooperation over time, as well as the multiple circulations between France and Africa in the audiovisual field during this period.
Keywords: African Research